Basilar Artery Dissection Presenting with Subarachnoid Hemorrhage: Report of Two Cases - Nakajima, Hideki (NMC Case Rep J, 2015)
Basilar artery dissection (BAD) presenting with subarachnoid hemorrhage (SAH) is life-threatening, but its treatment has not been established yet. We treated two patients with ruptured BAD. They were 40-year-old and 41-year-old women. Both of them were treated conservatively during the acute stage. In one patient, radiological abnormality of BAD improved spontaneously. In another patient, reconstructive endovascular treatment (stent with coiling) was required in the chronic stage because the lesion deteriorated morphologically. Neither of them suffered from rebleeding and both had favorable outcome. We reported two patients with ruptured BAD treated conservatively during the acute stage and their outcomes were favorable. We reviewed the literature of BAD presenting with SAH and discussed the management for these lesions.